(untitled) (Research, Society and Development, 2022)
The substitutive services created from the regulatory legislation of the Psychiatric Reform compete to overcome the hospital-centered, institutionalized model, starting with an intervention model that privileges integral and territorialized care. The CAPS occupies a strategic place in the Psychiatric Reform process and in the articulation of the mental health care network, increasing the capacity of the local teams to resolve mental health problems. This study aims to analyze the contributions that matrix support can provide for the expansion of an articulated network in mental health. A qualitative study was carried out using the technique of semi-structured interviews, according to some thematic axes. As a method of analysis, thematic analysis was used. The results indicate that CAPS need to work in articulation with the network of health services, assuming a strategic role in this articulation and in the constant weaving of the network. Substitute services do not cover Mental Health, so Primary Care should enter to expand mental health coverage. CAPS occupies a strategic place, to reorganize mental health in the territory. Finally, articulation with the health network as a whole and with the community is essential, providing comprehensive care; Enabling the exchange of knowledge and experiences, in addition to advising the basic health units.